Quantification of oligopeptide‐20 and oligopeptide‐24 in cosmetic creams using hydrophilic interaction liquid chromatography with electrospray ionization mass spectrometry. Issue 3 (20th February 2018) - Giannakou, Maria; Varvaresou, Athanasia; Kiriazopoulos, Evaggelos; Papageorgiou, Spiridon; Kavvalou, Eirini; Tsirivas, Efstathios; Panderi, Irene
Abstract: Peptides are a very popular category of cosmetic ingredients covering a wide range of applications in cosmetics. Hydrophilic interaction liquid chromatography is promising for the analysis and separation of such polar substances. In this work, the chromatographic behaviour of oligopeptide‐20 and oligopeptide‐24 was initially investigated on a zwitterionic ZIC®‐HILIC analytical column under isocratic elution with UV detection. Then, a hydrophilic interaction liquid chromatography with positive ion electrospray mass spectrometric assay was developed and validated for the quantitation of these peptides in cosmetic creams. All analytes were separated by using a polymeric zwitterionic ZIC®‐pHILIC analytical column (150.0 × 2.1 mm i.d., particle size 3.5 μm, 200 Å) with isocratic elution. The mobile phase was composed of a 28% 32.5 mM ammonium formate water solution pH 9.5 in acetonitrile and pumped at a flow rate of 0.25 mL min −1 . A run time of less than 11 min for each sample made it possible to analyze a large number of samples per day. This is the first reported application of hydrophilic interaction liquid chromatography in the simultaneous determination of oligopeptide‐20 and oligopeptide‐24 in cosmetic creams and it can be used to support routine quality control of these products.